The Relationship between Knowledge and Attitude of Women of Fertile Age with Papsmear Action - Hendrawati, Hendrawati; Septiana, Vinka; Wahdini, Morika (Global Health Science Group, 2023)
This research is titled Relationship of Knowledge and Relationship of with Papsmear Action This research type is quantitative research, that is descriptive analytic with cross sectional research design. Research Objective: To know relationship of knowledge and attitude of Fertile Age Women with action to do Papsmear in RT 05 RW 04 Kelurahan new triangle of sub-district Pancoran Mas Depok in 2022. The sample is the whole subject under study and is considered to represent the entire population of 75 women of childbearing age. In this research the data is taken directly from the respondents who will be examined by using the interview method, while the tool used to collect the data is a questionnaire in the form of checklist lists prepared by variable research, processing and data analysis done by editing, coding, entry, processing, tabulating . Data analysis includes univariate and bivariate. Chi-square test results show that the variable of knowledge has a significant relationship to the examination of pap smear, the knowledge of respondents with significant value p-value = 0.013 <α = 0.05 then it can be concluded that the existence of the knowledge of fertile women with the act of doing pap smear. Attitudes of respondents with significant value p-value = 0,000 <α = 0.05 then to the node that the relationship of female attitudes of childbearing age with the act of doing pap smear. Characteristics of respondents with significant value p-value = 0.096> α = 0.05 so it is stated that there is no relationship characteristics of fertile women with the act of doing pap smear.